Entrepreneurial orientation, social media affect SMEs marketing performance in West Borneo - Hendri, Markus; Fahruna, Yulyanti; Listiana, Erna; Barkah, Barkah; Rosnani, Titik (Junal Ilmu Manajemen, 2024)
This research investigates the influence of entrepreneurial orientation and the use of social media on the marketing capabilities and marketing performance of Small and Medium Enterprises (SMEs) in West Borneo. The results show that entrepreneurial orientation has a positive effect on marketing ability and marketing performance, while the use of social media has a positive impact on marketing ability. However, the use of social media does not have a significant effect on marketing performance. This research uses a five-point Likert scale and applies Structural Equation Modeling (SEM) with the AMOS 24 statistical tool. These findings provide insight for business owners and stakeholders in improving their marketing performance in the current digital era.